Endobronchial Metastasis of Renal Carcinoma: A Case Report and Review of Previous Literature - Zhang, Guang-Lei; Chen, Shu; Li, Jin-Dong; Wang, Chun-Guang (Frontiers in Surgery, 2021)
The definition of endobronchial metastasis (EBM) lacks clarity because it is currently based on the judgements of surgeons; it is rare in patients with non-pulmonary malignancies. Although EBM represents an advanced stage of malignancy, it does not necessarily indicate a poorer prognosis than that for its primary tumors. The present study defines EBM as bronchoscopy-visible lesions with histologically confirmed primary extrapulmonary tumors, excluding those primary lung tumors with involvement of the bronchial lumen. A bronchoscopy and biopsy provide strong proof for diagnosis. Complete surgical resection is the best choice for patients with EBM. This study analyzed the case of a 69-year-old male patient who had undergone a radical left nephrectomy several years previously after the identification of a bronchoscopy-visible lesion in the left main bronchus. The lesion was initially diagnosed as an angiogenic tumor but was eventually confirmed by surgical biopsy as EBM from the left kidney. After diagnosis, the patient underwent a left pneumonectomy. The analysis of this case focused on diagnosis, symptoms, radiographic findings, treatment, and prognosis. A review of the previous literature relating to EBM was also conducted.